"Spectra‐cular" Measurements: Confocal chromatic sensors offer modern technology allied with high speed and maximum precision and make them suitable for Industry 4.0. Issue 4 (9th October 2017) - Streicher, Alexander
Abstract: In a world of Industry 4.0, sensors must perform high‐speed measurements and provide high‐precision results in order to ensure reliable quality assurance. In particular, optical measurement technology is becoming more important for production and inspection processes, as it is non‐contact and independent of the target material and surface properties. This is a decisive advantage in a 'live' production process where tactile measurement technology is operating at its limits, particularly if the target is in a difficult‐to‐access area. Confocal chromatic sensors offer innovative technology, high speed and high precision.